Zum Adelsverständnis der Realisten des 19. Jahrhunderts im deutsch-polnischen Bereich (Theodor Fontane, Gustav Freytag, Marie v. Ebner Eschenbach) - Załubska, Cecylia (Studia Germanica Posnaniensia, 2018)
The names of the three writers mentioned in the title are representative for German realism of the 19th century. Their understanding of nobility was different as their social origins differed. The first two of them - Fontane and Freytag, both from the bourgeoisie spheres knew mainly the Prussian nobility, and obviously the Polish nobility, too, and Marie v. Ebner Eschenbach, a noblewoman by origin, was in the circles of Austrian aristocracy and hence comes her perfect knowledge of these circles. All three of them had a particular attitude towards Polish questions. Theodor Fontane was known for his liking of noblemen and great families which at the end of the last century, during the expansion of big industry and the growth of importance of the developing bourgeoisie, did not bring him recognition. A totally different point of view of nobility and Poles is presented by Gustav Freytag who was born at the Polish-German border (in Kluczbork). The one-sided subjective image which he draws in his novels, first of all in the best-seller Owes and has fulfills a tendentiously aimed task of slandering Poles, Polish economy (Polnische Wirtschaft) and of course of Polish nobility. The Austrian noblewoman, Marie von Ebner Eschenbach was the most competent person of all the three writers mentioned here as she knew the nobility from the inside. Her coming from the German-Slavic nobility (she was born the countess of Dubsky from the border of Bohemia and Moravia) did not let her become a chauvinist. In her prosa she is against the privileges of the nobility who are shown by her in a distorting mirror of the satire, and she shows the life of rural people with some fondness.